Penerapan Pendekatan PAIKEM (Aktif, Inovatif, Kreatif, Efektif dan Menyenangkan) pada Pembelajaran Pidato Persuasif: Suatu Kajian - Jeany Eva Krisna (Universitas Batanghari Jambi, 2020)
This study aims: 1) To know how the application of active, innovative, creative, effective, and fun learning called PAIKEM in Indonesian language learning for class IX Semester 1 KD.4.4, namely